Defining Lymphoplasmacytic Lymphoma: Does MYD88L265P Define a Pathologically Distinct Entity Among Patients With an IgM Paraprotein and Bone Marrow–Based Low-Grade B-Cell Lymphomas With Plasmacytic Differentiation?. Issue 2 (2nd June 2018) - Fang, Hong; Kapoor, Prashant; Gonsalves, Wilson I; Frederick, Lori A; Viswanatha, David; Howard, Matthew T; He, Rong; Morice, William G; McPhail, Ellen D; Greipp, Patricia T; Ansell, Stephen M; Kyle, Robert A; et al.
Abstract: Objectives: Lymphoplasmacytic lymphoma (LPL) remains a poorly defined entity, even with the discovery of MYD88 L265P mutations and association with Waldenström macroglobulinemia (WM). Among bone marrow (BM)–based, low-grade B-cell lymphoma with plasmacytic differentiation (LGBLPD) and immunoglobulin M (IgM) paraproteins, we sought to determine whether MYD88 L265P defines a distinct entity and can help refine diagnostic criteria for LPL. Methods: BMs diagnosed with LGBLPD or LPL and serum IgM paraprotein were studied (2007-2013). Clinicopathologic features were reviewed and specimens were tested for MYD88 L265P . Results: In total, 138 (87%) of 159 cases had MYD88 L265P, and 158 of 159 were clinically considered WM. MYD88 L265P cases had higher disease burden than MYD88 WT . Features associated with MYD88 L265P include increased mast cells and lymphocyte (not plasma cell)–predominant infiltrate. Hemosiderin, Dutcher bodies, and paratrabecular growth were not associated with MYD88 L265P . Conclusions: Our data support a clinicopathologic approach to LPL diagnosis and recognition that it may manifest with varying morphologies, phenotypes, and molecular features.